Time to recovery and its predictors among children aged 6–59 months having uncomplicated severe acute malnutrition attending an outpatient therapeutic program in Northeast Ethiopia: prospective cohort study - Feleke, Fentaw Wassie; Masresha, Setamlak Adane; Mulaw, Getahun Fentaw (Frontiers in Nutrition, 2024)
Introduction: There is less data regarding the variables influencing recovery times, despite the accessible outpatient therapy program (OTP) bringing services for the treatment of severe acute malnutrition (SAM) closer to the community. Therefore, this study aimed to identify the factors that influence the recovery duration in children with uncomplicated SAM between the ages of 6 and 59 months who were attending an OTP in North Wollo, northern Ethiopia. Methods: From February 2021 to July 2021, 356 children, ages 6-59 months, enrolled in a facility-based prospective cohort study. An interviewer administered a semi-structured questionnaire once a week to acquire anthropometric measures. The data were imported into Stata version 17 for analysis from EPI data entry version 4.6.06. The time to recovery for each attribute was determined using a log-rank test, a survival curve, and a Kaplan-Meier estimate of the median time to recovery. The Cox proportional hazards model was used to identify independent predictors of recovery time; statistical significance was indicated at 95% CI and a P-value of 0.05. Results: With a recovery rate of 74.7%, the median recovery period was 56 days. Frequency of growth monitoring and promotion (GMP) service utilization [AHR = 1.622 (95% CI:1.052 -2.130)], cough [AHR=0.385(95% CI: 0.176 -0.843)], maternal delivery at health center [AHR=1.448 (95%CI:1.023-2.050)], and maternal literacy [AHR=1.445(95% CI:1.019-2.058)] were determinants of time to recovery.A recovery rate of 74.7%, and 56 days (8 weeks) median recovery time were found. Maternal literacy, GMP frequency, maternal delivery at the health center, and cough at admission were independent predictors for this study. As a result, there should be a greater emphasis on the importance of girls' (future mothers') education and nutrition counseling, particularly the integration of GMP service components into institutional delivery/for girls/women who have received little education on how to improve time to recovery and the success of the OTP.